2008
DOI: 10.1007/s00101-008-1454-3
|View full text |Cite
|
Sign up to set email alerts
|

Besteht ein Zusammenhang zwischen der Einschätzung der Vitalgefährdung und der notfallmedizinischen Erfahrung des Notarztes?

Abstract: The results demonstrate that emergency physicians with less rescue experience rated the severity of illness or injury relatively lower in comparison to colleagues who had worked in the pre-hospital setting for many years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
8
0
4
Order By: Relevance
“…It is an observational, retrospective study in a specific local setting and, as stated above, not applicable to other dispatch systems or two-tier EMS. The NACA score is known to be described as subjective [24] and not always reproducible [25], and the patient’s condition may change for better or worse while the EMS is on its way, inducing incoherence between the dispatch and EMS findings on scene. Therefore it may not always describe the patient’s clinical state on EMS arrival on site, as a minority of patient worsen during EMS care or transport, wich may overestimate under-traige.…”
Section: Discussionmentioning
confidence: 99%
“…It is an observational, retrospective study in a specific local setting and, as stated above, not applicable to other dispatch systems or two-tier EMS. The NACA score is known to be described as subjective [24] and not always reproducible [25], and the patient’s condition may change for better or worse while the EMS is on its way, inducing incoherence between the dispatch and EMS findings on scene. Therefore it may not always describe the patient’s clinical state on EMS arrival on site, as a minority of patient worsen during EMS care or transport, wich may overestimate under-traige.…”
Section: Discussionmentioning
confidence: 99%
“…We used the NACA score to evaluate the patient’s severity status, as this score has been significantly correlated with short-term survival, transfer to the intensive care unit and hospital length of stay [ 17 19 ] although it has been described as partly subjective [ 30 ] and not always reproducible [ 31 ]. The NACA score defines the most serious clinical state experienced at any given time during the mission.…”
Section: Discussionmentioning
confidence: 99%
“…The experience and training level of the doctors that use the scoring system increases scoring quality according to a study by Knapp et al. 12 A study from the German ADAC Luftrettung service described the use of the NACA score as highly subjective and showed that even unequivocal conditions such as resuscitation and death, and clearly life-threatening diseases such as acute myocardial infarction, were all often found to be scored incorrectly. 13 …”
Section: Discussionmentioning
confidence: 99%